2006
DOI: 10.7152/acro.v17i1.12489
|View full text |Cite
|
Sign up to set email alerts
|

A Phenomenological Framework for the Relationship Between the Semantic Web and User-Centered Tagging Systems

Abstract: This paper uses Husserl's theory of phenomenology to provide a model for the relationship between user-centered tagging systems, such as del.icio.us, and the more highly structured systems of the Semantic Web. Using three aspects of phenomenological theory-the movement of the mind out towards an entity and then back in an act of reflection, multiplicities within unity, and the sharing of intentionalities within a community-the discussion suggests that both tagging systems and the Semantic Web foster an intersu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0
2

Year Published

2007
2007
2015
2015

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 5 publications
0
22
0
2
Order By: Relevance
“…Aquest coneixement reflecteix les opinions independents i diverses d'un grup de persones (Sunstein 2006). Les etiquetes d'aquesta folksonomy (Angeletou et al 2007) estan sovint força relacionades entre si, ja que poden ser utilitzades per un usuari per etiquetar recursos relacionats, o per diferents usuaris per etiquetar el mateix recurs (Wu, Zhang, and Yu 2006;Campbell 2006). Els patrons que sorgeixen d'aquestes pràctiques d'etiquetatge proporcionen, no només una manera d'organitzar la informació per als usuaris (Kipp and Campbell 2006), sinó també una capa de semàntica feble (Dye 2006) …”
Section: Feina Relacionadaunclassified
“…Aquest coneixement reflecteix les opinions independents i diverses d'un grup de persones (Sunstein 2006). Les etiquetes d'aquesta folksonomy (Angeletou et al 2007) estan sovint força relacionades entre si, ja que poden ser utilitzades per un usuari per etiquetar recursos relacionats, o per diferents usuaris per etiquetar el mateix recurs (Wu, Zhang, and Yu 2006;Campbell 2006). Els patrons que sorgeixen d'aquestes pràctiques d'etiquetatge proporcionen, no només una manera d'organitzar la informació per als usuaris (Kipp and Campbell 2006), sinó també una capa de semàntica feble (Dye 2006) …”
Section: Feina Relacionadaunclassified
“…Ferramentas que possibilitam que os usuários marquem suas páginas e atribuam etiquetas para representar seus temas de interesse (CAMPBELL, 2006).…”
Section: Social Bookmarkingunclassified
“…It has been suggested that a certain pattern will appear among individual tags created in the uncontrolled way if there is enough participation (when a lot of people tag the same item); that is, eventually some kind of structure will emerge in a bottom-up fashion. As Campbell (2006) puts it, the notion is, "if you let users tag their own resources in their own ways, with their own words, patterns of order will emerge; these patterns will be truer, more convincing, more user-centered, and more useful than the pattern imposed by formal classification schemes. What's more, they will acquire greater accuracy and greater sophistication as more and more people use them" (p. 4).…”
Section: Social Tagging As a Flexible Mechanism For Organizing Informmentioning
confidence: 99%